2017
DOI: 10.1017/s1355617717000170
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cognitive Impairment Subtypes in a Cohort of Elderly Essential Tremor Cases

Abstract: Objective Individuals with essential tremor (ET) exhibit a range of cognitive deficits generally conceptualized as “dysexecutive” or “fronto-subcortical,” and thought to reflect disrupted cortico-cerebellar networks. In light of emerging evidence that ET increases risk for Alzheimer’s disease (AD), it is critical to more closely examine the nature of specific cognitive deficits in ET, with particular attention to amnestic deficits that may signal early AD. Method We performed a cross-sectional analysis of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 63 publications
1
24
1
Order By: Relevance
“…Impairments of attention and working memory were commonly seen. A 2017 cross sectional analysis of 128 older patients with essential tremor found that both amnestic and non-amnestic mild cognitive impairment (MCI) subtypes were represented (n=24); amnestic MCI, single and multi-domain, represented about 70% (n=17) of cases 68. Multi-domain amnestic MCI was the most common subtype (n=13; 54%) Five neuropsychological tests that are sensitive to mild cognitive deficits in patients with essential tremor (as defined by a Clinical Dementia Rating of 0.5) are the California Verbal Learning Test II Total Recall, Logical Memory II, Verbal-Paired Associates I, category Switching Fluency, and Color-Word Inhibition 69…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Impairments of attention and working memory were commonly seen. A 2017 cross sectional analysis of 128 older patients with essential tremor found that both amnestic and non-amnestic mild cognitive impairment (MCI) subtypes were represented (n=24); amnestic MCI, single and multi-domain, represented about 70% (n=17) of cases 68. Multi-domain amnestic MCI was the most common subtype (n=13; 54%) Five neuropsychological tests that are sensitive to mild cognitive deficits in patients with essential tremor (as defined by a Clinical Dementia Rating of 0.5) are the California Verbal Learning Test II Total Recall, Logical Memory II, Verbal-Paired Associates I, category Switching Fluency, and Color-Word Inhibition 69…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Study Group et al, 2006b;Benito-León, Louis, Mitchell, & Bermejo-Pareja, 2011;Bermejo-Pareja et al, 2007;Cersonsky et al, 2018;Collins et al, 2017), depressive symptoms , personality changes (Thenganatt & Louis, 2012), changes in sleep patterns (Benito-León, Louis, & Bermejo-Pareja, 2013;Gerbin, Viner, & Louis, 2012), changes in visual reaction time (Jiménez-Jiménez et al, 2010), and hearing impairment Ondo, Sutton, Dat Vuong, Lai, & Jankovic, 2003).…”
Section: Louis Bermejo-pareja and Neurological Disorders In Central Smentioning
confidence: 99%
“…The current view of essential tremor (ET), one of the most common adult neurological disorders (Benito-León, 2009;Louis & Ferreira, 2010), is that it may be a family of diseases, unified by the presence of kinetic tremor, and characterized by etiological, clinical and pathological heterogeneity (Benito-León, 2014;Benito-León & Louis, 2006;. Aside from classic motor manifestations, ET is now considered a heterogeneous entity associated with a number of nonmotor manifestations, Sengul, Sengul, Sural, Bakim, & Forta, 2015) including cognitive disorders (Benito-León, Louis, Bermejo-Pareja, & Neurological Disorders in Central Spain Study Group, 2006a; Benito-León, Louis, Bermejo-Pareja, & Neurological Disorders in Central Spain Study Group et al, 2006b;Benito-León, Louis, Mitchell, & Bermejo-Pareja, 2011;Bermejo-Pareja et al, 2007;Cersonsky et al, 2018;Collins et al, 2017), depressive symptoms , personality changes (Thenganatt & Louis, 2012), changes in sleep patterns (Benito-León, Louis, & Bermejo-Pareja, 2013;Gerbin, Viner, & Louis, 2012), changes in visual reaction time (Jiménez-Jiménez et al, 2010), and hearing impairment Ondo, Sutton, Dat Vuong, Lai, & Jankovic, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive deficits are not uncommon, affecting 30–60% of patients ( 14 ), but run a wide range of severities from subclinical abnormalities to mild cognitive impairment (MCI) and dementia. Specific cognitive deficits in ET include impairments in executive function, working memory, verbal memory, and language ( 14 , 15 ). Furthermore, individuals with ET also experience increased frailty as they age ( 16 ), and psychosocial factors contribute to the difficulty of dealing with ET.…”
Section: Introductionmentioning
confidence: 99%